Nomenclatural survey of the genus Amaranthus (Amaranthaceae s.s.). 8. About Amaranthus polygonoides s.l. and A. anderssonii, two related taxa described from the tropical regions of America with notes on their taxonomy - Iamonico, Duilio (Instituto de Ecología, A.C., 2020)
Background and Aims: Amaranthus comprises 70-75 species of which about half are native to America. Some taxa are used as ornamentals, food or medicine and escape from cultivation, mainly causing economic impact to the agricultural systems. The genus is taxonomically critical due to its high phenotypic variability and hybridization that caused nomenclatural disorders. A note about Amaranthus polygonoides s.l. and A. anderssonii, whose nomenclature and taxonomy need to be still clarified, is presented. Methods: This work is based on examination of herbarium specimens and analysis of literature. Taxonomically relevant characters were measured (length and width (the widest part of the blade) of the leaves, longest and shortest diameters of the seeds, ratio length/width of the leaf blades and dehiscence/indehiscence of the fruits). The variability of the continuous characters was illustrated by box plots.Key results: The names Amaranthus polygonoides, A. anderssonii s.s., A. anderssonii f. erectus, A. taishanensis, Sarratia berlandieri, and Scleropus urceolatus are discussed. A specimen at BM-SL, that served as the base for the lectotype of A. polygonoides (Sloane’s illustration), was indicated. Previous holotype indications for Sarratia berlandieri and Scleropus urceolatus are corrected as lectotypes. Amaranthus taishanensis is confirmed to be a synonym of A. polygonoides s.s. The morphological study of leaves and seeds, as well as data about the distribution and the available phylogenetic analyses, show that the taxa can be distinguished at infraspecific ranks. A new classification is proposed recognizing a single species (A. polygonoides) with two subspecies, subsp. urceolatus comb. nov. and subsp. polygonoides. The latter taxon includes var. berlandieri comb. nov. and var. polygonoides.Conclusions: Amaranthus polygonoides s.l. and A. anderssonii are native to tropical regions of America, currently treated as separate taxa. The use of box plots, along with the available phylogenetic analyses, helped to clarify their taxonomy.